Analisis Informasi Laporan Arus Kas Untuk Mengukur Kinerja Keuangan Pada Pt Semen Indonesia (Persero) Tbk Periode 2014-2016 Yang Terdaftar Di Bursa Efek Indonesia - Aqnes Dwi Sakti Hamidah (Trunojoyo University of Madura, 2018)
PT. Semen Indonesia (Persero) Tbk reports cash flow reports annually to make use of cash flow report information as an important company performance analysis tool. One analysis of financial performance using cash flow statements is the ratio of cash flow statements. The purpose of this study is to find out how to analyze cash flow statements to measure financial performance at PT. Semen Indonesia (Persero) Tbk from 2014 to 2016. This study uses data analysis techniques with qualitative descriptive methods, namely by calculating the ratio of operating cash flows, the ratio of cash coverage to current debt, the ratio of capital expenditure, the ratio of total debt, the ratio of cash to interest coverage , and the ratio of the flow of funds. The results of this study indicate that financial performance at PT. Semen Indonesia (Persero) Tbk in 2014 to 2016 is where from six ratios are calculated into two ratios that meet the standards of more than one, namely the CKB and CAD ratios and the other four ratios are below one. Means that all cash flows owned by the company only have more potential to pay short- term liabilities.